Inclusive Education of Children with Special Needs: Practices, Opportunities and Barriers - Muhammad Usman, Mushtaq Ahmad, Mumtaz Ali (JIE, 2023)
The study was to explore the status of inclusive education, its opportunities and barriers in primary schools in Punjab. The objectives of the study were to (i) Find out inclusive education practices in primary schools in Punjab, (ii) Find out opportunities of inclusive education in primary schools in Punjab and (iii) Explore the barriers of inclusive education in primary schools in Punjab. T